THE EFFECTS OF FLIPPED CLASSROOM LEARNING MANAGEMENT ON ACADEMIC ACHIEVEMENT AND SELF-REGULATION ABILITY OF MASTER’S DEGREE STUDENTS - Manee-on, Samaporn (Journal of Educational Review Faculty of Education in MCU, 2025)
This research article aimed to 1) develop the learning achievement according to the flipped classroom concept of master’s degree students to meet the criteria of 80 percent, 2) compare the self-regulation ability of master’s degree students between studying using the flipped classroom concept and conventional learning, and 3) compare the satisfaction of master’s degree students between studying using the flipped classroom concept and conventional learning. The sample group consisted of 2 classes of 44 students from the Master of Education Program in Curriculum and Instruction, first year, studying in the second semester of the academic year 2024, using the cluster random sampling method. The instruments consisted of 1) documents on learning management based on the flipped classroom concept, 2) an assessment form for master’s degree students’ academic achievement, 3) an assessment form for self-regulation ability of master’s degree students, and 4) an assessment form for students’ academic satisfaction towards learning management based on the flipped classroom concept compared to traditional learning management. Data were analyzed by finding percentages, means, standard deviations, and testing hypotheses using the independent t-test. The results of the study found that: 1) The academic achievement of the master’s degree students who learned according to the flipped classroom concept during the study had a score of 83.33 percent and after the study had a score of 86.13 percent, which was higher than the specified criteria of 80 percent. 2) The results of the comparison of self-regulation ability of students between learning according to the flipped classroom concept and learning in a normal way were significantly different at the .01 level. Students who learned according to the flipped classroom concept had higher self-regulation ability than students who learned in a normal way. 3) The results of the comparison of student satisfaction between learning according to the flipped classroom concept and learning in a normal way were significantly different at the .01 level. Students who learned according to the flipped classroom concept had higher satisfaction than students who learned in a normal way.